Applications of nanomaterials in tissue engineering. Issue 31 (26th May 2021) - Zheng, Xinmin; Zhang, Pan; Fu, Zhenxiang; Meng, Siyu; Dai, Liangliang; Yang, Hui
Abstract : Scientific description about the types, synthesis, functionalization, characterization application, challenges and prospects of nanomaterials in tissue engineering. Abstract : Recent advancement in nanotechnology has brought prominent benefits in tissue engineering, which has been used to repair or reconstruct damaged tissues or organs and design smart drug delivery systems. With numerous applications of nanomaterials in tissue engineering, it is vital to choose appropriate nanomaterials for different tissue engineering applications because of the tissue heterogeneity. Indeed, the use of nanomaterials in tissue engineering is directly determined by the choice. In this review, we mainly introduced the use of nanomaterials in tissue engineering. First, the basic characteristics, preparation and characterization methods of the types of nanomaterials are introduced briefly, followed by a detailed description of the application and research progress of nanomaterials in tissue engineering and drug delivery. Finally, the existing challenges and prospects for future applications of nanomaterials in tissue engineering are discussed.